Exercise and skeletal muscle regeneration - Kurosaka, M.; Machida, S. (The Journal of Physical Fitness and Sports Medicine, 2012)
Skeletal muscle injury is generally caused by stimuli, such as intense resistance training, eccentric muscle contraction, muscle strain and bruising. Injured skeletal muscles are repaired within several weeks after injury, because skeletal muscle has a remarkable capacity for muscle regeneration. Cellular and molecular events underlying the regenerative processes are mainly regulated by myogenic stem cells and inflammatory cells. The aim of this review is to summarize the current understanding of the cellular and molecular mechanisms responsible for muscle regeneration. In this review, focus will be given to the critical roles of satellite cells and macrophages during muscle regeneration. In addition, the satellite cell responses to exercise are also discussed.